Armstrong on Probabilistic Laws of Nature. (2nd September 2017) - Jacobs, Jonathan D.; Hartman, Robert J.
Abstract: D. M. Armstrong famously claims that deterministic laws of nature are contingent relations between universals and that his account can also be straightforwardly extended to irreducibly probabilistic laws of nature. For the most part, philosophers have neglected to scrutinize Armstrong's account of probabilistic laws. This is surprising precisely because his own claims about probabilistic laws make it unclear just what he takes them to be. We offer three interpretations of what Armstrong-style probabilistic laws are, and argue that all three interpretations are incompatible either with some feature of Armstrong's broader metaphysics or with essential features of his account of laws (or both).